Ultra-fine quantitative removal of silicon materials by femtosecond laser - Tong Chen; Jiang Li; Pengna Wei; Aifei Pan; Haiping Liu (AIP Advances)
The development of miniaturized electronic devices is highly dependent on precision manufacturing techniques. To achieve device miniaturization, material removal and processing accuracy down to the submicrometer or even nanometer level are required. The precision machining of the mass block, a key component of the silicon micro-gyroscope, is taken as a reference. To achieve the precision positioning function of the micro-gyroscope, the mass at a certain position of the Si-based mass block must be precisely controlled. Therefore, the ultra-fine quantitative removal process of silicon materials is studied. A femtosecond laser processing system is constructed, and the evolution of micro–nanostructure and etching depth on the silicon surface is explored. An ultra-fine quantitative removal process is developed to achieve quantitative removal of different etching depths on the silicon surface. The experimental results show that the minimum removal thickness can be 0.502 µm. The processing index requirement for a silicon surface removal thickness of less than 0.001 mm has been fulfilled. It is critical to resolve the issue of high-quality manufacturing of miniaturized silicon-based devices.